Information literacy focused on school librarian activities - Ottonicar, Selma Leticia Capinzaiki (2019)
Information literacy is important to access, evaluate and use information in an efficient way. Furthermore, information literacy helps individuals to use technology, to seek information, to interpret a text, to verify an information source and to produce new knowledge. This paper aims to discuss how information literacy contributes to the development of public policy for school libraries. The public policy should focus on librarians’ lifelong learning. The methodological procedures involve a bibliographical research about information literacy and public policy in the context of school libraries. Therefore, we researched materials like books, printed and digital articles in many journals in the information science field. In conclusion, we illustrated that information literacy needs to be considered in public policy of school libraries in Brazil, so that this literacy can guide information professionals and improve the services offered by the libraries.